Effect of SiO2 Methyl Modification on the Performance of Nondispersible Underwater Concrete and Reinforcement Mechanism - Weiqiu Zhong; Longlong Zheng; Yongkang Shen; Wuxu Li; Lingwei Zeng (Advances in Civil Engineering)
The effect of SiO2 methyl modification (CH3-NS) on various properties of the nondispersible underwater concrete (UWC) was evaluated. The fluidity and antiwashout resistance of the UWC mixture were evaluated by various tests. Concrete specimens were designed in the two different damage states, i.e., P-type and Z-type. The compressive strength test, contact angle test, Fourier transform infrared spectroscopy (FTIR), and scanning electron microscopy (SEM) techniques were performed to analyze them. The experimental results showed that adding CH3-NS increased the fluidity of the UWC. When too much CH3-NS was added, the antiwashout resistance was reduced The CH3-NS doping should not exceed 3.0%. For P-type specimens, adding uncalcined CH3-NS improved the strength of the reinforced specimens compared to calcined CH3-NS, the value was 17.9%. And the peak and ultimate stresses of the specimens were shifted forward by 18.1 and 4.8%, respectively. The polar force component magnitude of the surface tension of the specimen was the major factor affecting the surface free energy of P-type specimens. Different CH3-NS statuses and the properties of specimens were the major factors affecting the surface free energy of Z-type specimens. Contact angle measurements, FTIR, and SEM showed that uncalcined CH3-NS enhanced the hydrophobicity and reduced the surface free energy while increasing the density of UWC and thus enhancing its compressive strength.